Harmonizing cyberlaws and regulations : the experience of the East African community - Fredriksson, Tobrjorn (UN New YorkUS, 2012)
Assesses the status of cyber-legislation in the EAC. Discusses the need for regional harmonisation and the challenges faced with regard to the implementation of cyberlaws in the EAC region. Gives a detailed account of the status of the legislation in each country.